Very Low-Volume, High-Intensity Interval Training Mitigates Negative Health Impacts of COVID-19 Pandemic-Induced Physical Inactivity - Reljic, Dejan; Eichhorn, Annalena; Herrmann, Hans J.; Neurath, Markus; Zopf, Yurdagül (International Journal of Environmental Research and Public Health, 2022)
Initially, we aimed to investigate the impact of a one-year worksite low-volume, high-intensity interval training (LOW-HIIT) on cardiometabolic health in 114 sedentary office workers. Due to the COVID-19 pandemic outbreak, LOW-HIIT was discontinued after 6 months and participants were followed up for 6 months to analyze physical activity/exercise behavior and outcome changes during lockdown. Health examinations, including cardiopulmonary exercise testing and the assessment of cardiometabolic markers were performed baseline (T-1), after 6 months (T-2, termination of worksite LOW-HIIT) and 12 months (T-3, follow-up). Cycle ergometer LOW-HIIT (5 x 1 min at 85-95% HRmax) was performed 2x/week. For follow-up analyses, participants were classified into three groups: HIIT-group (continued home-based LOW-HIIT), EX-group (continued other home-based exercises), and NO-EX-group (discontinued LOW-HIIT/exercise). At T-2, VO2max (+1.5 mL/kg/min, p = 0.002), mean arterial blood pressure (MAB, -4 mmHg, p < 0.001), HbA(1c) (-0.2%, p = 0.005) and self-reported quality of life (QoL, +5 points, p < 0.001) were improved. At T-3, HIIT-group maintained VO2max and QoL and further improved MAB. EX-group maintained MAB and QoL but experienced a VO2max decrease. In NON-EX, VO2max, MAB and QoL deteriorated. We conclude that LOW-HIIT can be considered a promising option to improve cardiometabolic health in real-life conditions and to mitigate physical inactivity-related negative health impacts during lockdowns.
CRIS-Team WoS Importer:2022-10-21